(untitled) (Proceedings of Faculty of Civil Engineering, 2025)
This paper investigates the mechanical behaviour of T-joints made from cold-formed steel C-profiles connected with self-tapping screws, with a particular emphasis on the influence of profile thickness and hole design on the joint’s load-bearing capacity. Joints with two sheet thicknesses, 0.95 mm and 1.15 mm, as well as two hole variants, without reinforcement and with reinforcement, achieved by plastic forming, were analysed. Numerical simulations were performed using ABAQUS software, and the validity of the models was confirmed by comparison with relevant results from the literature. The results show that increasing the sheet thickness by approximately 21% results in a 15.2% increase in the maximum load capacity of the joint, accompanied by a change in the failure mechanism, where the critical failure location shifts from the steel profiles to the screw. Introducing hole reinforcement significantly improves stress distribution and reduces local deformations around the screw holes. For thinner profiles, reinforcement leads to a 19.8% increase in load capacity, while for thicker sheets, the increase is considerably more pronounced, reaching 46.7%. Thus, hole reinforcement enhances the joint’s resistance to local deformations and enables better utilization of the steel profiles’ capacity without exceeding their yield limit. Proper selection of sheet thickness, screw quality, and hole design proves crucial to ensuring optimal load capacity and safety of T-joints in thin-walled steel structures. The obtained results provide a valuable contribution to the understanding and optimization of joints in modern cold-formed steel constructions.